DEVELOPING ADDIE MODEL-BASED ESP COURSEBOOK - Luluk Iswati (Universitas Kuningan, 2019)
Coursebook plays a substantial role in facilitating teaching and learning process, especially for EFL (English as a Foreign Language) learners of English for Specific Purposes (ESP). However, the widely available coursebooks do not always match with the designed program and the learners' as well as the institution' needs. To ensure that a coursebook can optimally support the goals of an ESP course, developing materials is suggested. This research aimed to develop an ESP coursebook using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. A Research and Development method was employed in this research in which the data were collected through questionnaire and interview. The questionnaire was distributed to 430 Business English 1 students at Universitas Muhammadiyah Yogyakarta. Meanwhile, the interview was conducted to 4 English teachers. Here, the data were obtained during the first and the last steps of ADDIE model (analysis and evaluation). The data obtained from the analysis phase were used for need analysis, while those obtained from the evaluation phase were used to evaluate the strengths and weaknesses of the coursebook. The findings showed the coursebook's elements which cover language, content, tasks, learners, and the learning are good, but the visual elements highly need improvement.